Study on the Correlation etween the Discrimination Index, B Facilitation Value and Distractor Efficiency of a Formative Assessment Useful Tools for OBE Practices - Kumar B.R, Arun (Journal of Engineering Education Transformations, 2022)
Different assessment tools are used to assess engineering knowledge and skills. Multiple choice questions (MCQs) and regular internal tests are commonly used techniques for assessing students. But often the imperfections in the framing of the question can affect students’ results and impede the objective of evaluating their knowledge. In this article, the method of evaluating the quality of MCQs and internal test questions framed for PG students in a programming language was considered. For the analysis, Kelly’s method was included by considering fast learning group and slow learning groups performances in both the methods of evaluation. Facilitation value, discrimination index, and distraction efficiency were estimated for the items attempted by the group of MCA students. The results obtained show that the item analysis provided necessary data for improvement in question formulation and helped in reviewing the quality of items and tests also. Questions having a lower difficulty index were significantly associated with a higher discrimination index and higher distractor efficiency.